IMF Staff papers : Volume 30 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1983)
This paper reviews the channels of macroeconomic interdependence under flexible exchange rates. The model emphasizes the linkage of international capital markets, expectations, and nominal and real wage stickiness in affecting the impact of disturbances on employment, prices, and the exchange rate. The standard rational-expectations macroeconomic model is extended to facilitate analysis of the role of risk premiums created by imperfect asset substitutability. Peso problems and bubbles are discussed briefly. The paper discusses two alternative proposals designed to deal with the exchange rate implications of policy interdependence. One is the McKinnon proposal for world monetarism; the other is the band proposal. Both proposals are rejected because they fail to cope with the problems of the transition to a low, common inflation rate. The paper concludes with the suggestion that improved performance of the world economy cannot come from a better exchange rate system but rather from a more systematic use of incomes policies.